2009
DOI: 10.1371/journal.pone.0006013
|View full text |Cite
|
Sign up to set email alerts
|

Human Telomere Length Correlates to the Size of the Associated Chromosome Arm

Abstract: The majority of human telomere length studies have focused on the overall length of telomeres within a cell. In fact, very few studies have examined telomere length for individual chromosome arms. The objective of this study was to examine the relationship between chromosome arm size and the relative length of the associated telomere. Quantitative Fluorescence In Situ Hybridization (Q-FISH) was used to measure the relative telomere length of each chromosome arm in metaphases from cultured lymphocytes of 17 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
0
17
2
Order By: Relevance
“…Long telomeres have been found in many longlived vertebrates, including turtles [Hatase et al, 2008], birds and some mammals [Haussmann et al, 2003]. Some studies have suggested a positive correlation between telomere length and total chromosome or arm length [Zijlmans et al, 1997;Sridevi et al, 2002;Wise et al, 2009]; however, our results do not support this observation. In tuatara, the size of microchromosomal telomeres is equivalent to or longer than those of the macrochromosomes ( fig.…”
Section: Telomerescontrasting
confidence: 99%
“…Long telomeres have been found in many longlived vertebrates, including turtles [Hatase et al, 2008], birds and some mammals [Haussmann et al, 2003]. Some studies have suggested a positive correlation between telomere length and total chromosome or arm length [Zijlmans et al, 1997;Sridevi et al, 2002;Wise et al, 2009]; however, our results do not support this observation. In tuatara, the size of microchromosomal telomeres is equivalent to or longer than those of the macrochromosomes ( fig.…”
Section: Telomerescontrasting
confidence: 99%
“…Thus, the large number of microchromosomes might, at least partly, explain the high prevalence of ultralong telomeres in great tits. Note that this explanation contrasts with the positive correlation between chromosome size and TL observed in the human genome (Wise et al, 2009). On the other hand, the smallest human chromosome (no.…”
Section: Discussionmentioning
confidence: 79%
“…Again, telomeres more distant from centromeres were longer. Further analysis revealed a significant positive correlation between individual chromosome arms and telomere length: longer arms had longer telomeres than shorter arms [Wise et al, 2009]. Thus, similar to mouse acrocentric chromosomes, human chromosomes which are predominantly submetacentric show longer telomeres at q-arms than at parms suggesting that centromere position may affect telomere length.…”
Section: Chromosome-specific Telomere Length Regulationmentioning
confidence: 86%